Considerations regarding the EC Regulation no. 261/2004 from the perspective of the protection of passengers, but also of air transport operators - Bularca Anca Roxana (Bulletin of the Transilvania University of Braşov, 2021)
The study regarding the interpretation and application of the provisions of the EC Regulation no. 261/2004 aims to highlight theoretical and practical aspects outlined since the entry into force of this normative act and until now. The European legislator has adopted this normative act, with direct binding force for the member states of the European Union, in order to ensure a protection of passengers who have concluded air transport contracts with different effective air transport operators. In essence, passengers are consumers and air carriers are in a dominant position, as a contracting party, in this type of contract, which is usually one of accession. However, the interpretation and application of this normative act in the different Member States has generated non-unitary practices from the perspective of the terms defined by the Regulation, but also unfair practices in the sense of forming an immoral market in which the right to compensation is traded.